(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The research aimed to reveal the extent of blended education’s contribution to enhancing the concepts of the French language subject from the students’ perspective in blended education schools in Latakia Governorate, and to uncover the differences among the research sample of students regarding the extent of blended education’s contribution to enhancing the concepts of the French language subject based on (educational stage and sex). The descriptive methodology was used, and a questionnaire was designed consisting of (46) statements, which was applied to a sample of (134) students. The results showed that the overall contribution of blended education in enhancing the concepts of the French language subject from the students’ perspective in blended education schools in Latakia Governorate was average. It also indicated that there were no significant and substantive differences between the average scores of the research sample based on the sex, while there were significant and substantive differences based on the educational stage in favor of secondary stage students. The research provided several recommendations: Continuous training for French language teachers on the skills of using blended learning in teaching French, equipping schools with computers in accordance with the number of students, and connecting them to the internet.